Chemical and physical parameters of Portuguese honey : classification of Citrus, Erica, Lavandula and Eucalyptus honeys by multivariate analysis and FTIR-ATR spectroscopy - Anjos, O. (2010)
Trabalho apresentado na 3rd Scientific Conference of Institute of Tropics and Subtropics, que decorreu em Novembro de 2009 em Praga.